Harmonization of Commercial Law: Patterns of Positivization and the Formulation of DSN-MUI Fatwas in Realizing Legal Certainty for Islamic Banking in Indonesia - Baidhowi Baidhowi; Ahmad Rofiq; Ali Murtadho; Rayi Kharisma Rajib (Journal of Private and Commercial Law, 2026)
The rapid development of the Islamic banking industry in Indonesia requires commercial legal instruments that not only ensure sharia compliance but also provide positive legal certainty for business actors. This article analyses the harmonization of Islamic commercial law into the national legal system through the mechanism of positivizing the fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) into Law No. 21 of 2008 on Islamic Banking and the Compilation of Sharia Economic Law (KHES). Through normative legal research methods employing statutory, conceptual, and comparative approaches, this study elaborates the ontological transformation of fatwas—from cultural authority (i'laniyah) into imperative legal norms (mulzim). The findings indicate that harmonization is carried out through institutional integration (the Islamic Banking Committee) and normative integration (adoption, adaptation, and expansion) into the regulations of Bank Indonesia and the Financial Services Authority. The formulation of commercial contracts incorporates the principle of freedom of contract (mabda' hurriyah al-ta'aqud) as well as classical fiqh doctrines through the instruments of maslahah mursalah, takhayyur, and talfiq. This material legal certainty is reinforced by the readiness of formal law through the expansion of the absolute jurisdiction of the Religious Courts and the National Sharia Arbitration Board (Basyarnas) following Constitutional Court Decision No. 93/PUU-X/2012. In conclusion, the positivization of DSN-MUI fatwas has successfully eliminated the operational ambiguity of sharia contracts and created a sustainable business ecosystem. This transformation directly contributes to achieving the Sustainable Development Goals (SDGs), particularly SDG 8 (Inclusive Economic Growth) and SDG 16 (Strong Judicial Institutions and Access to Justice), by providing consumer protection and absolute certainty in the enforcement of proprietary rights within Indonesia.